Numerical Analysis of the Lamb Metacarpal Bone: Approximation of Bending Tests - İbrahim Kutay Yılmazçoban (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In the development of newstrategies for fracture ﬁxation, new methods have to be tested biomechanicallyunder in vitro conditions before clinical trials can be performed. Severalrecent developments, including tensile, compressive, and bending tests freshwhole bone specimens, offer the possibility to understand animal bonesmechanical behavior. Therefore, the aims of the present study were to determinethe effects of three point bending tests on the lamb metacarpal bones atdifferent speeds and determine the mechanical properties of bone and to comparethese properties with the finite element analysis of the tests. 12 specimenswere obtained from 1 year old Ankara curly lambs. Three point bending testswere conducted using three different compression speeds to assess and comparebone fracture properties. From the test results bending moments, stresses,strains and deformations were calculated for three different compressionspeeds. Finite Element Analysis results were compared to the test results.Because of the use fresh bone specimens of an animal part are used like in vivotests in biomechanical studies, investigating failure loads of the metacarpusby bending tests and numerical analysis are guiding for clinical operations andcomputer simulations.